Capital mobility and economic growth in South Africa - Dhlamini, Nonceba Michelle (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
The South African current account balance has been deteriorating over the years. An investigation of the correlation between capital mobility and economic growth is of interest as South Africa is heavily reliant on capital inflows to finance the current account deficit. This research topic is of importance as there is need to devise policies that maximise the benefits the nation derives from capital mobility. The benefits that capital flows provide economies, theoretically outweigh the disadvantages, provided that capital flows are absorbed productively. The topic is also of interest in the light of the magnitude of shocks to the South African economy such as the rand crisis, dotcom bubble, stock market bubble, inflation targeting, commodity super cycle, global financial crisis, the Covid-19 pandemic and Russo-Ukrainian War, as these shocks have translated to slower economic growth and higher levels of inflation. These shocks have equally revealed that countries need to have sound macroeconomic policies in order to survive the impact of any crises. The vision 2030 secretariat has identified capital markets as the key providers of capital required for achieving social economic blueprint. The empirical evidence locally is limited in comparison to the empirical evidence from outside of South Africa. This topic is of importance as South African studies on this topic are not as recent and this study aims to bridge that gap. Data were obtained from the South African Reserve Bank Quarterly Bulletin and the World Bank database for the period 1990 to 2022. The Autoregressive Distribution Lag model was employed in order to determine the relationship. This study relied on the supply-leading theory which posits capital markets may positively or negatively affect key indicators of economic growth. The study found that there is a positive long run relationship between net capital flows, saving-investment ratio and economic growth and a negative long run relationship between the degree of trade openness and economic growth. The findings will allow opportunity to address capital flow surges and in turn boost investor confidence. Capital flow management measures can help manage destabilizing exchange rate movements and capital flows coupled with macroprudential tools helping reduce the domestic buildup of vulnerabilities.
Keywords: Capital movements -- South Africa; Economic development -- South Africa; Autoregression (Statistics); Econometric models; Financial crises